FREKUENSI PEMUTARAN TELUR UNTUK MENINGKATKAN DAYA TETAS, FERTILITAS, MORTALITAS TELUR PUYUH (coturnix coturnix japonica) - miki suhadi; Riko Herdiansah; Novi Eka Wati (Wahana Peternakan, 2022)
One of the influencing factors in hatching is egg screening. This study aims to determine the frequency of egg turning to increase hatchability, fertility, and mortality of quail eggs. Completely randomized design (CRD) is the design used in this study and the experiment in the study which consisted of 4 treatments and 5 replications. The treatments of this study were: 1 screening/day for each replication (p0), 2 screenings/day for each replication (p1), 3 screenings/day for each replication (p2), 4 screenings/day for each replication (p3). From the results of this study, it was concluded that the frequency of three rotations per day on quail eggs showed the highest percentage yield at 100% hatchability, while the highest percentage of fertility was 84%, and the lowest percentage of mortality was 19%. Keywords: Turning eggs, hatchability, fertility, mortality